ROCK inhibition with Y-27632 reduces joint inflammation and damage in serum-induced arthritis model and decreases in vitro osteoclastogenesis in patients with early arthritis - Rodríguez-Trillo, Angela; Pena, Carmen; García, Samuel; Pérez-Pampín, Eva; Rodríguez-López, Marina; Mera-Varela, Antonio; González, Antonio; Conde, Carmen (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a common chronic inflammatory disease affecting primarily peripheral joints, which is only partially controlled with current treatments. RA leads to pain, disability, deformities, and life expectancy shortening. Its pathogenesis is complex involving multiple cell types and signaling pathways that we incompletely understand. One of the pathways we have elucidated starts with WNT5A signaling and contributes to the aggressive phenotype of the RA synoviocytes through RYK-RhoA/ROCK signaling. Now, we have explored the contribution of ROCK to arthritis in vivo, using the K/BxN serum-transfer arthritis model; and to osteoclastogenesis, using the arthritis model and cells from patients with inflammatory arthritis. The mice and cells were treated with the specific ROCK inhibitor Y-27632 that caused a significant improvement of arthritis and reduction of osteoclastogenesis. The improvement in mouse arthritis was observed in the clinical evaluation and, histologically, in synovial inflammation, cartilage damage, bone erosion, and the abundance of multinucleated TRAP+ cells. Expression of inflammatory mediators in the arthritic joints, as assessed by real-time PCR, was also significantly reduced. The ROCK effect on bone was confirmed with in vitro assays using bone marrow precursors of arthritic mice and peripheral blood monocytes of patients with inflammatory arthritis. These assays showed dramatically reduced osteoclastogenesis and bone resorption. Overall, our findings suggest that ROCK inhibition could be part of a therapeutic strategy for RA by its dual action on inflammation and bone erosion.